2004
DOI: 10.1563/0.693.1
|View full text |Cite
|
Sign up to set email alerts
|

Human Histologic Analysis of Mineralized Bone Allograft (Puros) Placement Before Implant Surgery

Abstract: Because clinicians are placing more dental implants, it is becoming more important to maintain bone volume after tooth extraction. This article discusses the various bone-augmentation materials available to the clinician and illustrates a case report of particulate mineralized bone allograft (Puros) placement after extraction. Exposure of the grafted site after 5 months revealed a hard bony structure. Human histologic analysis at the light microscopic level revealed nonvital spicules of mature calcified bone h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 13 publications
3
30
0
7
Order By: Relevance
“…These osteoconductive bone substitutes become integrated into the newly formed bone matrix [20]. In this study, we used MCBA based on encouraging documented reports of new bone formation [21]. Our histological results were consistent with those of Noumbissi et al [22], Froum et al [23] and Schmitt et al [13].…”
Section: Discussionsupporting
confidence: 85%
“…These osteoconductive bone substitutes become integrated into the newly formed bone matrix [20]. In this study, we used MCBA based on encouraging documented reports of new bone formation [21]. Our histological results were consistent with those of Noumbissi et al [22], Froum et al [23] and Schmitt et al [13].…”
Section: Discussionsupporting
confidence: 85%
“…[13][14][15] However, the literature is not conclusive on the best material to use as a graft. The studies have reported the use of different materials, including autologous bone, 11,[15][16][17][18][19] homologous bone, [20][21][22][23][24] xenografts, 14,15,19,25 and alloplastic materials. 1,14,25,26 Within these alternative, the autologous bone is the one with the closest to ideal conditions, 2, 27-29 but due to the disadvantage of a second surgical site donor and the morbidity this entails, the exploration of other alternatives was necessary.…”
Section: -11mentioning
confidence: 99%
“…[13][14][15] No obstante, la literatura no es concluyente sobre el tipo de material ideal para utilizar como injerto. Los estudios han reportado el uso de diversos materiales, dentro de los cuales podemos citar el hueso autólogo, 11,[15][16][17][18][19] el hueso homólogo, [20][21][22][23][24] los xenoinjertos 14,15,19,25 y los materiales aloplásticos. 1,14,25,26 Dentro de estas opciones, el hueso autólogo es el que presenta las condiciones más cercanas a las ideales, 2,[27][28][29] pero debido a la desventaja de un segundo sitio quirúr-gico donante y a la morbilidad que esto acarrea, se hizo necesaria la exploración de las otras opciones.…”
Section: Introductionunclassified
See 2 more Smart Citations